EFEKTIFITAS KOMBINASI TERAPI AKUPUNTUR DAN REBUSAN TEH HIJAU DALAM MENURUNKAN KADAR GLUKOSA PADA PASIEN DIABETES TIPE 2 - Anindini Winda Amalia; Jessi Suryani Setiawan (Universitas Respati Yogyakarta, 2020)
Background: diabetes mellitus type 2is one of the major health problems in the world. Uncontrolled diabetes mellitus can cause serious complications such as kidney disease, vision problems, cardiovascular disease and leg amputations that contribute to morbidity and mortality in diabetic patients. There are various approaches to treat and prevent diabetes and its secondary complications, one of which is a combination of acupuncture therapy and green tea stew.Objective: to determine the effectiveness of the combination of acupuncture therapy and green tea stew in reducing glucose levels in patients with type 2 diabetes.Methods: The design of this study was quasi-experimental, the sample size was 30 people divided into three groups, 10 people (received acupuncture therapy), 10 people (got green tea stew), and 10 people (acupuncture and green tea combination). The intervention was carried out for 4 weeks, with acupuncture therapy 2 times a week and drinking green tea stew 2 times a day. Analyze data to find out the differences between groups of interventions using the ANOVA test.Results: The results of this study were obtained by ANOVA test at week 2 with p value 0.016 and at week 4 with p value 0.002 (p <0.05), which means there were differences in the amount of glucose in patients with type 2 diabetes mellitus given acupuncture combination and green tea stew with only acupuncture or green tea stew.Conclusion: there is a difference in the amount of glucose in patients with type 2 diabetes mellitus who are given a combination of acupuncture and green tea stew with those who are only given acupuncture or green tea stew.